الصياغة الإسلامية لعلم الاجتماع بين دواعي التنمية وإمكانيات التطبيق - لوحيدي, فوزي; جلول, أحمد (University of Eloued جامعة الوادي, 2016)
إن المسلم إذا أراد صياغة علم الاجتماع صياغة إسلامية عليه أن ينطلق من نظرة الإسلام للكون والحياة و الإنسان ، كما أن عليه أن يبتعد عن عملية التلفيق بان ينطلق من مصطلحات غربية ويوظفها توظيفا إسلاميا ، وقد جاءت هذه الدراسة محاولة البحث في المنطلقات الفكرية لبناء نظرية في علم الاجتماع على أصول إسلامية بحتة ، تبحث في المسألة بين الدواعي التي تحث عليها وإمكانية تطبيقها في عصر صراع الأفكار والعولمة If Muslim wants to formulate sociology from an Islamic point of view he has to start from the way Islam views the universe and life and the human being. In addition, he also needs to be distant from the fabrication process that stems from the Western terminology and trying to "Islamize" them. This study attempts to look at the intellectual premises for the construction of the theory in the sociology based on purely Islamic origins, looking at the issue of reasoning urging them and their applicability in the era of globalization and the struggle of ideas.
The Islamic drafting of Sociology Between the reasons of development and application possibilities
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الصياغة الإسلامية ، علم الاجتماع، القيم الإسلامية; Islamic drafting, sociology, Islamic values.